The Role of Guidance and Guidance Teachers in Developing Students' Cognitive Potential at SMP Muhammadiyah 16 Lubuk Pakam - br sembiring, rahlina; Lesmana, Gusman; Purba, Nita Widiyanti (Jurnal Riset Ilmu Pendidikan, 2023)
This study aims to understand how guidance and counseling can develop students' cognitive potential. This study uses the literature review method, which refers to the opinions of experts and the results of previous studies. Guidance and counseling in schools does not only aim to overcome student difficulties, but also assist school leaders, teachers and parents in understanding students in more depth. This research is descriptive qualitative research. The sampling techniques that are often used are purposive sampling and snowball sampling. The sample in this study consisted of counseling teachers and students at SMP 16 Muhammadiyah. Thus, guidance and counseling can be carried out in a more systematic and quality manner, and have the functions of understanding, prevention, alleviation, maintenance and development. The functions of guidance and counseling teachers include: 1) Providing assistance to students to optimally develop their potential, 2) Providing guidance and counseling support services and activities that focus on understanding, prevention, alleviation, maintenance, and self-development of students, 3) Providing assistance to related parties, such as parents, educators, or other interested parties, in accordance with the development and life of students, and 4) Functioning in planning, for example assisting students in making difficult choices regarding continuing education or the right career